2012
DOI: 10.1016/j.joca.2012.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Shearing of synovial fluid activates latent TGF-β

Abstract: Objective TGF-β is synthesized in an inactive latent complex that is unable to bind to membrane receptors, thus unable to induce a cellular biological response until it has been activated. In addition to activation by chemical mediators, recent studies have demonstrated that mechanical forces may activate latent TGF-β via integrin-mediated cellular contractions, or mechanical shearing of blood serum. Since TGF-β is present in synovial fluid in latent form, and since normal diarthrodial joint function produces … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
72
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(74 citation statements)
references
References 48 publications
(60 reference statements)
1
72
1
Order By: Relevance
“…Other work on synovial joint biomechanics such as wear testing protocols specifying bovine serum as the lubricant (Harsha and Joyce 2011) point to the inclusion of serum as a relevant physiological parameter for in vitro model systems, as synovial fluid is an ultrafiltrate of plasma and includes growth factors found in serum (Denko, Boja et al 1996). Our team has studied the maintenance of native cartilage explants in synovial fluid (Albro, Durney et al 2014), and shown that shearing of native synovial fluid can activate growth factors such as latent TGF-beta that may modulate biological behavior of the surrounding joint tissues (Albro, Cigan et al 2012). Future work will include shear studies using native synovial fluid as the perfusion media to investigate FLS mechanosensitivity in a more physiologic model system.…”
Section: Discussionmentioning
confidence: 99%
“…Other work on synovial joint biomechanics such as wear testing protocols specifying bovine serum as the lubricant (Harsha and Joyce 2011) point to the inclusion of serum as a relevant physiological parameter for in vitro model systems, as synovial fluid is an ultrafiltrate of plasma and includes growth factors found in serum (Denko, Boja et al 1996). Our team has studied the maintenance of native cartilage explants in synovial fluid (Albro, Durney et al 2014), and shown that shearing of native synovial fluid can activate growth factors such as latent TGF-beta that may modulate biological behavior of the surrounding joint tissues (Albro, Cigan et al 2012). Future work will include shear studies using native synovial fluid as the perfusion media to investigate FLS mechanosensitivity in a more physiologic model system.…”
Section: Discussionmentioning
confidence: 99%
“…1,28,[81][82][83] To avoid an adverse effect of TGF-b1, one possibility is that moderate local activation of latent TGF-b1 found in native synovial fluid by chemical or mechanical forces may provide the necessary cues to stimulate migration if combined with PDGF-BB. 84,85 Alternatively, engineering approaches designed to locally deliver exogenous latent rather than active TGF-b1 have shown promising preliminary results in rats. 86 A strong local dose of a prochemotactic GF (e.g., PDGF-BB), however, may be sufficient to induce a chemotactic effect similar to that observed in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…11 Subsequently, Albro et al independently confirmed that shear stress can activate latent TGF-β1 in synovial fluid. 13 We recently reported that mice with targeted deletion of TGF-β1 in their megakaryocytes and platelets are partially protected from developing cardiac hypertrophy, fibrosis and systolic dysfunction, in response to constriction of the transverse aorta, a model that has increases WSS at the stenosis created and in the innominate artery. 14 Collectively, these data raise the possibility of an association between the activation of circulating latent TGF-β1 under high shear stress and the development of AS.…”
Section: Introductionmentioning
confidence: 99%